Evaluation of the magnitude of gastro-oesophageal reflux in Barrett's oesophagus. Issue 9 (September 1990) - Parrilla, P; Ortiz, A; Martinez de Haro, L F; Aguayo, J L; Ramirez, P
Abstract : A manometric study to determine the role of gastro-oesophageal reflux in Barrett's oesophagus was performed on 20 patients with Barrett's oesophagus and 53 patients with reflux oesophagitis without Barrett's oesophagus (25 with mild oesophagitis and 28 with severe oesophagitis). For the same reason, the 20 patients with Barrett's oesophagus also underwent 24 hour continuous oesophageal pH monitoring, and the results obtained were compared with those of 20 oesophagitis patients without Barrett's oesophagus (10 with mild oesophagitis and 10 with severe oesophagitis). The manometric results show that the motor changes found in the Barrett's group are specific but similar to the motor dysfunction associated with reflux oesophagitis. Motor anomalies are probably related more to the inflammatory process in the oesophageal wall than to the metaplastic changes themselves. The pH monitoring results show that while reflux in the Barrett's oesophagus patients was greater overall than in the oesophagitis group without Barrett's oesophagus, the changes are similar when the results are compared with the severe oesophagitis group. In conclusion there are other factors besides gastro-oesophageal reflux involved in the pathogenesis of Barrett's oesophagus.